Entrenchment and the Psychology of Language Learning: How We Reorganize and Adapt Linguistic Knowledge. 2017
DOI: 10.1037/15969-017
|View full text |Cite
|
Sign up to set email alerts
|

Entrenchment and language attrition.

Abstract: In cognitive linguistics it is assumed that the strength of entrenchment of linguistic knowledge in human memory has a direct impact on the way that such knowledge is structured and processed: more deeply entrenched knowledge will be represented more holistically and processed more automatically. At the same time, this view implies that linguistic knowledge may erode if certain memory traces are not used for longer periods of time. This process of deterioration is called language attrition, but it is unclear h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…Like other memory representations, linguistic knowledge is also thought to be retained through such a process of memory consolidation (Takashima & Bakker, ). The neurocognitive process of strengthening the representation of linguistic knowledge is also in accordance with the concept of entrenchment (Langacker, ), which postulates that repeated exposure to a native language results in solid memory consolidation (deeply entrenched knowledge), while disuse leads to disentrenchment, mainly caused by the weakening of the neural connections storing linguistic knowledge (Steinkrauss & Schmid, ; Yoshitomi, ).…”
Section: Background To the Studymentioning
confidence: 89%
See 1 more Smart Citation
“…Like other memory representations, linguistic knowledge is also thought to be retained through such a process of memory consolidation (Takashima & Bakker, ). The neurocognitive process of strengthening the representation of linguistic knowledge is also in accordance with the concept of entrenchment (Langacker, ), which postulates that repeated exposure to a native language results in solid memory consolidation (deeply entrenched knowledge), while disuse leads to disentrenchment, mainly caused by the weakening of the neural connections storing linguistic knowledge (Steinkrauss & Schmid, ; Yoshitomi, ).…”
Section: Background To the Studymentioning
confidence: 89%
“…Despite intensive research on neurocognition of language, still little is known about the timing of linguistic consolidation, that is, about the time it takes for (native) linguistic knowledge to fully stabilize and to reach a saturation threshold after which disuse of the language no longer affects the speaker's linguistic competence. What is known from L1 attrition research is that this point of “saturation,” at which the linguistic competence of native speakers becomes consolidated, is “situated substantially later than the age at which individual grammatical features are usually taken to become target‐like (typically between ages 2 and 6)” (Steinkrauss & Schmid, , p. 378) and much earlier than adulthood.…”
Section: Background To the Studymentioning
confidence: 99%
“…For instance, detachment from a 2L1 or L2-dominant language environment creates a unique setting in which one can test whether a (native) language involves the acquisition of linguistic knowledge, followed by a period of stabilization. This idea originates from memory consolidation in neurocognition, which hypothesizes that memory is consolidated through recurrence and recency of neuronal activity (Yoshitomi, 1992;Steinkrauss & Schmid, 2016). Disuse of a language before its consolidation causes neural connections responsible for storing linguistic knowledge to weaken and thus results in language attrition.…”
Section: Who Are Returnees?mentioning
confidence: 99%
“…Results indicated that the speakers were faster to name the pictures in their L1 in the first years after immigration, but eventually became faster in their L2. These results strongly suggest that language use and entrenchment are closely related, with frequent use of a given construction strengthening its entrenchment and extended periods of disuse weakening it (Langacker, 1987(Langacker, , 2016Schmid, 2016;Steinkrauss & Schmid, 2016).…”
Section: Introductionmentioning
confidence: 96%